BMPR1B gene in brachydactyly type 2–A family with de novo R486W mutation and a disease phenotype - Marcin Bednarek (Molecular Genetics & Genomic Medicine, 2021)
Abstract Background Brachydactylies are a group of inherited conditions, characterized mainly by the presence of shortened fingers and toes. Based on the patients’ phenotypes, brachydactylies have been subdivided into 10 subtypes. In this study, we have identified a family with two members affected by brachydactyly type A2 (BDA2). BDA2 is caused by mutations in three genes: BMPR1B, BMP2 or GDF5. So far only two studies have reported the BDA2 cases caused by mutations in the BMPR1B gene. Methods We employed next‐generation sequencing to identify mutations in culpable genes. Results and Conclusion In this paper, we report a case of BDA2 resulting from the presence of a heterozygous c.1456C>T, p.Arg486Trp variant in BMPR1B, which was previously associated with BDA2. The next generation sequencing analysis of the patients’ family revealed that the mutation occurred de novo in the proband and was transmitted to his 26‐month‐old son. Although the same variant was confirmed in both patients, their phenotypes were different with more severe manifestation of the disease in the adult.